2022
DOI: 10.55446/ije.2022.166
|View full text |Cite
|
Sign up to set email alerts
|

Black Soldier Fly Hermetia illucens (L.): Ideal Environmental Conditions and Rearing Strategies

Abstract: Endeavours to recycle organic waste utilizing black soldier fly (BSF) Hermetia illucens (L.) into waste management and high nutrient biomass development have indeed picked up momentum recently. But there is not much data on their appropriate rearing conditions. Very few studies delineating the fecundity and reproduction capacities of BSFs concluded that the presence of natural sunlight or artificial light with intensity of 110-200 μ mol m2s-1 and above triggers mating and oviposition (about 85-90 %) at success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…The observed adverse effect of air humidity on phosphorus accumulation in our study might be attributed to its potential to limit microbial activity essential for nutrient mineralization and organic matter decomposition. Previous studies [39][40][41] have demonstrated that the optimal air humidity range for BSFL typically falls within 40% to 70%. Thus, deviations from this range can impact the nutrient cycling in the composting system.…”
Section: Phosphorus and Potassium Accumulation In Frass Fertilizer As...mentioning
confidence: 99%
“…The observed adverse effect of air humidity on phosphorus accumulation in our study might be attributed to its potential to limit microbial activity essential for nutrient mineralization and organic matter decomposition. Previous studies [39][40][41] have demonstrated that the optimal air humidity range for BSFL typically falls within 40% to 70%. Thus, deviations from this range can impact the nutrient cycling in the composting system.…”
Section: Phosphorus and Potassium Accumulation In Frass Fertilizer As...mentioning
confidence: 99%